Modelo de Datos de Producción Cartográfica del SIGAM, Escalas 1:250.000 Y 1:100.000 - Pedreira Junco, José Ángel (2018)
Fil: Pedreira Júnco, Juan Ángel. SADIM: Sociedad Asturiana de Diversificación Minera; España.